2019
DOI: 10.33758/mbi.v14i3.321
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Inflation Influence Toward the Number of Foreign Tourists Visiting Indonesia and Their Impact on Indonesia’s Economic Growth

Abstract: The tourism sector is one of the potential contributors to GDP in Indonesia. So the number of foreign tourists visiting Indonesia is considered to have a major influence on Indonesia's economic growth. The acceleration of the tourism sector has made the tourism sector attractive to study. .In addition, inflation is also considered to have an influence on the number of foreign tourists and economic growth. This research was conducted to determine whether or not there was an effect of inflation on the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Nonetheless, price increases normally lower demand (Varian 1999), especially in sectors such as tourism where demand is highly sensitive to price variations (Sancho 1998). Effectively, in the case of Indonesia, it has been found that inflation has a negative impact on international tourist arrivals (Sulasmiyati 2018). Meanwhile, in Mexico, high inflation rates have slowed down investment in tourism due to increases in the cost of water, electricity, and fuel (Forbes Staff 2022).…”
Section: Tourism Employment and Inflationmentioning
confidence: 99%
“…Nonetheless, price increases normally lower demand (Varian 1999), especially in sectors such as tourism where demand is highly sensitive to price variations (Sancho 1998). Effectively, in the case of Indonesia, it has been found that inflation has a negative impact on international tourist arrivals (Sulasmiyati 2018). Meanwhile, in Mexico, high inflation rates have slowed down investment in tourism due to increases in the cost of water, electricity, and fuel (Forbes Staff 2022).…”
Section: Tourism Employment and Inflationmentioning
confidence: 99%
“…Due to the reduction in purchasing power, tourism economic activities are hindered. Inflation factors have been proven to harm the number of foreign tourist visits; therefore, the government must effectively control national inflation (Sulasmiyati, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it has generated US$ 14.11 billion in foreign exchange until 2018 (Statistics Indonesia, 2020). It comes from the flights, hotels, restaurants, and products from Micro, Small, and Medium Enterprises that are all the sources of foreign exchange revenues for tourism (MSMEs) (Sulasmiyati, 2019). This industry also employs a large number of people, supporting the local economies.…”
Section: Introductionmentioning
confidence: 99%
“…This industry also employs a large number of people, supporting the local economies. The Indonesian government predicted that foreign tourists would contribute to 20 million visits per year, out of a total foreign exchange of US$ 17.6 billion (Sulasmiyati, 2019). Nonetheless, the contribution of tourism to GDP has remained stable at roughly 4% per year from 2015 to 2017 (Statistics Indonesia, 2018).…”
Section: Introductionmentioning
confidence: 99%